การดำเนินงานของรัฐบาลไทยในการแก้ไขปัญหาเรื่อง เอชไอวี/เอดส์ ตามปฏิญญาว่าด้วยพันธกรณีเรื่องโรคเอดส์ในประเด็นด้านสิทธิมนุษยชน พ.ศ. 2544-2548 - วิชนันท์ยา เรืองโพธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The aim of this thesis is to study the international cooperation in solving the problem of HIV/AIDS which a global security issue in the contemporary world. The study emphasizes on the progress of the implementation of the Thai government in compliance with the Declaration of Commitment on HIV/AIDS during 2001-2005 especially in human rights aspects, including its results and obstacles. The conceptual frameworks for the study are based on the Neoliberalism concept of international cooperation and rights-based approach. The study finds that Thai government has improved the policy implementation in compliance with the declaration in certain areas such as providing ART to 50,000 people living with HIV/AIDS through the NAPHA by the end of the year 2004, initiating the policy to protect labour’s rights in working places by notification of the Ministry of Labour on the code of practice on prevention and management of HIV/AIDS in the establishment in 2005, and drafting the code to protect the rights of people living with HIV/AIDS and AIDS patient as well. However, the implementations of the Thai government in human rights aspects were quite inefficient particularly in terms of the government’s legal enforcement against violations of rights, free trade policies affecting human rights promotion, insufficient allocation of the budgets and resources for marginalized people, lack of participation of rights holder in decision-making process, lack of the information about how the problems affect people and their rights, etc. This study also finds that the obstacles were due to government policies, budgets, attitudes, and the bureaucratic system.